Contribution to the study on chemical constituents of Hedyotis auricularia L., (Rubiaceae) - Kim Tuyen, Pham Nguyen; Phi Phung, Nguyen Kim; Hung, Pham Dinh (Vietnam Journal of Chemistry, 2014)
From the whole plant of Hedyotis auricularia L., a new glycoside, 1’-deoxy-6’-O-(1-hydroxymethyl-2-hydroxy-1-methoxy)ethylglucopyranoside (1) was isolated along with 1’-O-ethyl-β-D-galactopyranoside (2), 2-formyl-5-hydroxymethylfuran (3), stigmasta-5,22-diene-3-O-β-D-glucopyranoside (4), ursolic acid (5) and oleanolic acid (6). Among them (1), (2), (3), (4)were the first time known to be present in this plant